Pengaruh Konflik Politik Terhadap Studi Hadis Pasca Perang Shiffin - Muhammad Muhammad Anshori (Jurnal Living Hadis, 2018)
This paper attempts to explain the phenomenon of hadith studies during the Ṣiffīn war. In the history of Islamic civilization, conflict is always there, one factor that raises conflict is political associated with leadership issue. Even the first conflict occurred in Islam had it after the Prophet Muhammad died. This factor influenced relatively to the study of hadith. Islamic history has experienced "bitter notes" since many wars deployed many companions of the Prophet (ṣaḥābah). They, who are considered fair in the Hadith narration, seemed to have desire to rule, and for the sake of power, they were willing to fight each other. Despite various reasons of religious importance and doctrines, this historical accident has affected to even our recent study of the source. This was renewed after the occurrence of the al-fitnah kubrā, which culminated in the battle of Ṣiffīn between 'Alī bin Abū Ṭālib and Mu'āwiyah ibn Abū Sufyān in 37 AH. Atleast after this war, the study of hadith experienced quite rapid development with the emergence of various kinds of the sect, group or current flow in Islam.